PERSEPSI MASYARAKAT TERHADAP KEBIJAKAN POLITIK DI KOTAMADYA MEDAN - PIN PIN . (JURNAL ILMIAH KOHESI, 2020)
In the world of politics, the role of political ethics cannot be ignored. This is related to, political morality is useful to investigate what constitutes good and bad, virtue, legal validity, truth of conscience, political moral obligations and so on. The reality of the problem faced in political culture is the gap between Political interference and the bureaucrat's (Administrator) independence regarding service management to the community. Then, there are attitudes and behaviors that are "negative", both politicians and bureaucrats in carrying out their respective functions. The purpose of this study is to identify and respond / people's attitudes towards the development of conditions and situations of political culture in the Municipality of Medan.The method used is a sample survey with the analysis unit of the voting community. Respondents were taken by stratified random sampling from the people of the Municipality of Medan. The research instrument was an interview guide and a questionnaire. The analysis used is descriptive qualitative data.The results showed that overall, both the lower, middle, and upper layers, considered that the ethics of politicians in Medan Municipality was relatively poor, namely 191 (63.67%) of the 300 respondents. And the respondent's reason is that after becoming politicians, they tend to be individual or think about their own interests, family and / or party as seen from the policies they gave birth to. That was very different from the campaign time. In conclusion, in realizing political participation in the Medan Municipality, the community has two characteristics or forms of political participation based on the nature of being mobilized and autonomous. Then, to assess how political ethics in the Medan Municipality, there are three patterns of individual attitudes and orientations towards politics, namely: (1). Cognitive Orientation: knowledge, belief (2). Affective Orientation: related feelings, involvement, rejection and the like about political objects, and (3). Evaluation Orientation: judgments and opinions about political objects that usually involvestandard values of political objects and events.